A simple strategy to prepare a layer-by-layer assembled composite of Ni–Co LDHs on polypyrrole/rGO for a high specific capacitance supercapacitor. Issue 69 (6th December 2019) - Kulandaivalu, Shalini; Hussein, Mohd Zobir; Mohamad Jaafar, Adila; Mohd Abdah, Muhammad Amirul Aizat; Azman, Nur Hawa Nabilah; Sulaiman, Yusran
Abstract : A facile and novel electrode material of nickel–cobalt layered double hydroxides (Ni–Co LDHs) layered on polypyrrole/reduced graphene oxide (PPy/rGO) is fabricated for a symmetrical supercapacitor via chemical polymerization, hydrothermal and vacuum filtration. Abstract : A facile and novel electrode material of nickel–cobalt layered double hydroxides (Ni–Co LDHs) layered on polypyrrole/reduced graphene oxide (PPy/rGO) is fabricated for a symmetrical supercapacitor via chemical polymerization, hydrothermal and vacuum filtration. This conscientiously layered composition is free from any binder or surfactants which is highly favorable for supercapacitors. The PPy/rGO serves as an ideal backbone for Ni–Co LDHs to form a free-standing electrode for a high-performance supercapacitor and enhanced the overall structural stability of the film. The well-designed layered nanostructures and high electrochemical activity from the hexagonal-flakes like Ni–Co LDHs provide large electroactive sites for the charge storage process. The specific capacitance (1018 F g −1 at 10 mV s −1 ) and specific energy (46.5 W h kg −1 at 464.9 W kg −1 ) obtained for the PPy/rGO|Ni–Co LDHs symmetrical electrode in the current study are the best reported for the two-electrode system for PPy- and LDHs-based composites. The outstanding performance in the prepared LBL film is a result of the LBL architecture of the film and the combined effect of redox reaction and electrical double layer capacitance.